2016
DOI: 10.1371/journal.pone.0165810
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Throughput Next-Generation Sequencing for HLA Typing on Buccal Extracted DNA: Results from over 10,000 Donor Recruitment Samples

Abstract: BackgroundUnambiguous HLA typing is important in hematopoietic stem cell transplantation (HSCT), HLA disease association studies, and solid organ transplantation. However, current molecular typing methods only interrogate the antigen recognition site (ARS) of HLA genes, resulting in many cis-trans ambiguities that require additional typing methods to resolve. Here we report high-resolution HLA typing of 10,063 National Marrow Donor Program (NMDP) registry donors using long-range PCR by next generation sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…These were easily detected due to non‐common linkage disequilibrium. Most studies have reported very low allele dropout frequencies (<1%), whereas others have reported frequencies as high as 10%, especially for the HLA‐DQB1 locus . Therefore, the need for alternative methods to confirm apparently homozygous HLA alleles is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…These were easily detected due to non‐common linkage disequilibrium. Most studies have reported very low allele dropout frequencies (<1%), whereas others have reported frequencies as high as 10%, especially for the HLA‐DQB1 locus . Therefore, the need for alternative methods to confirm apparently homozygous HLA alleles is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…These algorithms base their predictions on the frequency of haplotypes in the unrelated donor population. The increased utilization of DNA sequencing for typing registry populations has provided higher resolution HLA assignments, speeding donor selection. The application of next generation DNA sequencing to compile full length sequences of HLA genes has improved the ability to interpret sequencing results .…”
Section: Hla Class I Allele Frequencies In Matchis Volunteers (N = mentioning
confidence: 99%
“…This DNA sample was typed for HLA loci‐A, ‐B, ‐C, ‐DRB1, and ‐DQB1 using our routine NGS‐based HLA typing protocol covering full length of HLA‐A, ‐B, and ‐C, and exons 2 and 3 for HLA‐DRB1 and HLA‐DQB1 . Briefly, genomic DNA was extracted from a buccal swab sample, amplified, and sequenced on MiSeq (Illumina, SanDiego, California).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…This DNA sample was typed for HLA loci-A, -B, -C, -DRB1, and -DQB1 using our routine NGS-based HLA typing protocol covering full length of HLA-A, -B, and -C, and exons 2 and 3 for HLA-DRB1 and HLA-DQB1. 2 Briefly, genomic DNA was extracted from a buccal swab sample, amplified, and sequenced on MiSeq (Illumina, SanDiego, California). The results showed the HLA typing of this individual to be HLA-A*24:02:01, HLA-A*66new; HLA-B*18:01:01, HLA-B*44:03:01; HLA-C*04:01:01, HLA-C*07:01:01; HLA-DQB1*06:02, HLA-DQB1*06:02; and HLA-DRB1*11:04, HLA-DRB1*15:01 analyzed using NGSengine v2.4.0 (GenDx, Utrecht, The Netherlands) and HLA Twin v1.0.7 (Omixon, Budapest, Hungary).…”
mentioning
confidence: 99%